Hanbury Brown–Twiss approach for imaging through a dynamic scattering medium - Chandra S.; Sarkar T.; Kumar R.; Das B.; Singh R.K. (My University, 2025)
The Hanbury Brown–Twiss approach, associated with the correlation of intensity fluctuations at two different points in a wave field, unveils fundamental aspects of light. Here, we propose and experimentally demonstrate an imaging and phase recovery technique through a dynamic scattering medium using the Hanbury Brown–Twiss approach. A detailed theoretical basis is presented and verified by experimental demonstrations. To validate the application of the proposed technique, the randomness of the dynamically scattered light is exploited using temporal ergodicity for evaluating the correlation of intensity fluctuations and consequently applying it in the reconstruction of the object hidden behind the dynamic diffuser. © 2023 Optica Publishing Group.